1991
DOI: 10.1007/bf01073449
|View full text |Cite
|
Sign up to set email alerts
|

Hospice nurses' knowledge and attitudes toward the near-death experience

Abstract: I surveyed 60 hospice nurses regarding their knowledge and attitudes toward the near-death experience (NDE), using Thornburg's Near Death Phenomena Knowledge and Attitudes Questionnaire. Most hospice nurses had previous work experience with an NDEr. Approximately half the nurses were knowledgeable about the NDE. All participants had a positive attitude toward near-death phenomena and toward caring for an NDEr. Rec ommendations include near-death phenomena inservice education for hospice nurses and inclusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Other literature has supported this, highlighting the emotional or spiritual issues that may be raised following DBP, the impact of DBP, and that training and knowledge can help health professionals to support patients and/or families with issues that are not always understood, and with which clinicians are not always confident in responding to. (Barnett 1991, Serdahely et al 1988, Lawrence and Repede 2012. Barbato and colleagues (1999) found that the issue of DBP disclosure was problematic, with none of the 10 subjects in the study sharing their experience with a health care professional.…”
Section: Health Professional Responsementioning
confidence: 99%
“…Other literature has supported this, highlighting the emotional or spiritual issues that may be raised following DBP, the impact of DBP, and that training and knowledge can help health professionals to support patients and/or families with issues that are not always understood, and with which clinicians are not always confident in responding to. (Barnett 1991, Serdahely et al 1988, Lawrence and Repede 2012. Barbato and colleagues (1999) found that the issue of DBP disclosure was problematic, with none of the 10 subjects in the study sharing their experience with a health care professional.…”
Section: Health Professional Responsementioning
confidence: 99%
“…Literature regarding studies that assessed knowledge and attitudes of health care professionals toward the NDE is limited. There have been three studies that focused on various nursing specialties' atti tudes toward NDE (Barnett, 1991;Oakes, 1981;Thornburg, 1988); one study that assessed psychologists' knowledge of and attitudes to ward the NDE (Walker and Russell, 1989); and two studies to inves tigate the knowledge and attitudes of clergy regarding the NDE (Royse, 1985;Bechtel, Chen, Pierce, and Walker, 1992). There has been no study that assessed physicians' knowledge of and attitudes toward near-death experiences.…”
Section: Journal Of Near-death Studiesmentioning
confidence: 99%
“…These views and reactions reflect a negative attitude toward NDEs and NDErs that seems to derive from incomplete or inaccurate knowledge about the phenomenon and those who experience it. Despite the importance of this topic for thousands of NDErs' wellbeing, a review of the professional literature revealed only six published studies in English of health professionals' knowledge of and attitudes about NDEs: four involving medical health providers, three of nurses (Barnett, 1991;Bucher, Wimbush, Hardie, & Hayes, 1997;Cunico, 2001) and one of physicians (Moore, 1994); one involving psychologists (Walker & Russell, 1989); one involving clergy (Bechtel, Chen, Pierce, & Walker, 1992); one involving a mixture of physicians, nurses, and pastoral healthcare providers (Goedhart, 2011); and none involving counselors or other health professionals (Foster et al, 2009).…”
mentioning
confidence: 99%
“…In most published studies of knowledge and attitudes about NDEs, researchers either used or adapted Thornburg's instrument (Barnett, 1991;Bechtel et al, 1992;Bucher et al, 1997;Cunico, 2001;Moore, 1994;Walker & Russell, 1989). In a recent study of Dutch healthcare professionals' general and care-specific attitudes toward NDEs, Sandra Goedhart (2011) found Thornburg's instrument to be dated and of questionable validity (p. 8).…”
mentioning
confidence: 99%